Social stress and asthma: The role of corticosteroid insensitivity - Haczku, Angela (2010)
Psychosocial stress alters susceptibility to infectious and systemic illnesses and may enhance airway inflammation in asthma by modulating immune cell function through neural and hormonal pathways. Stress activates the hypothalamic-pituitary-adrenal (HPA) axis. Release of endogenous glucocorticoids, as a consequence, may play a prominent role in altering the airway immune homeostasis. Despite substantial corticosteroid and catecholamine plasma levels, chronic psychosocial stress evokes asthma exacerbations. Animal studies suggest that social stress induces corticosteroid insensitivity that in part may be due to impaired glucocorticoid receptor (GR) expression and/or function. Such mechanisms likely promote and amplify airway inflammation in response to infections, allergen or irritant exposure. This review discusses evidence of an altered corticosteroid responsive state as a consequence of chronic psychosocial stress. Elucidation of the mechanisms of stress-induced impairment of glucocorticoid responsiveness and immune homeostasis may identify novel therapeutic targets that could improve asthma management.